Piano Classic Collection of Pieces for the Intermediate Grades - FISCHER (ed.) (J. Fischer & Bro., 1949)
Di dalam buku ini terdapat lagu: Minuet in G Major (No.1); Minuet in G Minor (No.1); Bourree; Vivace; Elfin Dance; Sonatina in G; Musette in D; Minuet in D Minor; Etude in A; Grandmother's Minuet; Sonatina; Two dances; Minuet in G Major (no.2); Minuet in G Minor (no.2); By the Spring; Merry Farmer; Polonaise; Bagatelle in A minor; Albumblatt; Mazurka; Prelude in C major and prelude in C minor; Ecossaise; Solfeggietto; bgatelle; Two Etudes; Tambourine; Wild Horseman; Gavotte in G minor; Ecossiases in B Minor; Curious Story; Adagio in B Minor; Sonatina; Etude; Valse Moderato; Rondo Alla Turca; Presto; Etude; Etude in B minor; French Serenade; Moment Musical; Allegro in G major; Albumleaf waltz in A minor; Albumleaf fantastie dance; three ecossaises